The influence of varicocelectomy on semen parameters and fertility - Stasieczek, Mateusz; Bar, Krzysztof; Mitura, Przemysław; Dzierżak, Wojciech; Barczentewicz, Maciej; Janicki, Konrad; Bobiarski, Piotr; Jach-Siwek, Barbara; Kempisty, Jakub (Journal of Education, Health and Sport, 2019)
Introduction. Varicocele is an abnormal dilation of the spermatic veins within the pampiniform plexus of the spermatic cord. This pathology is diagnosed in 25% of infertile men. There is some data that confirms varicocelectomy improves semen parameters and fertility potential in men with clinically diagnosed varicocele and impaired semen parameters. The aim of our study was to determine the influence of laparoscopic varicocelectomy on semen parameters and evaluation of spontaneous pregnancy rate. Material and methods. We retrospectively reviewed the data of 60 consecutive patients subjected to laparoscopic varicocelectomy between November 2010 and December 2016 due to clinical varicocele, impaired semen parameters and infertility. Results. The average age was 31 +/- 7. Compared with baseline semen parameters, sperm count, sperm concentration, morphology and progressive motility at 3 and 6 months. We did not observe changes in semen volume and semen pH during follow-up. A total improvement in semen parameters was observed in 64% and 70% of patients after 3 and 6 months after surgery. In 4 patients deterioration of semen parameters was noticed. Spontaneous pregnancy was achieved in 30% of couples. Two pregnancies were unsuccessful due to spontaneous abortion. A total of 16 children were born. The surgery- to- conception time was 7.7 +/- 7 months. Conclusions. Laparoscopic varicocelectomy in a patient who has suffered from infertility and confirmed semen parameters and fertility potential of men.